Effect of process parameters on the rheological properties of banana (Musa acuminata) fiber and optimization using response surface methodology - Shubham Pandey; R.K. Naik; Vinay Kumar Pandey; Shivangi Srivastava; Gulden Goksen; Shivam Pandey; Sarvesh Rustagi (Journal of Agriculture and Food Research)
The labor-intensive, time-consuming, and uneconomical nature of manually extracting banana (Musa acuminata) fibers from pseudo-stem sheaths has prompted the exploration of automation as a solution. This study focuses on automating the feeding process of banana pseudostem sheaths using a quick return mechanism, which is more effective than other approaches. A comprehensive study was conducted to assess the impact of key process parameters, namely the decorticator (480–540 rpm), roller speed (50–80 rpm), and clearance between rollers (2–4 mm), on the mechanical properties of the extracted banana fiber. The Response Surface Methodology (RSM) was employed for the experimental design and analysis of data, and the mechanical properties under investigation included the tensile strength, Young's modulus, and strain percentage of the banana fiber. The results revealed that the decorticator speed, roller speed, and clearance between rollers are significantly influenced by their mechanical properties. Herein, the optimal process parameter values are identified as follows: a decorticator speed of 510 rpm, roller speed of 65 rpm, and clearance of 3 mm between rollers. The mechanical characterization of the optimized banana fiber exhibited impressive properties, with an ultimate tensile strength of 679.48 MPa, Young's modulus of 25.47 GPa, and strain of 3 %. This study demonstrates that automation coupled with systematic parameter optimization can enhance the mechanical attributes of banana fibers. This research not only addresses the challenges of manual extraction, but also advances the understanding of how process parameters affect banana fiber quality, thereby facilitating the utilization of this natural fiber in various industrial applications.